Changes in oral health behaviours between childhood and adolescence: Findings from a UK cohort study. Issue 5 (13th June 2019) - Leary, Sam D.; Do, Loc Giang
Abstract: Objective: Oral health is an important part of general health and well‐being. Health behaviours may change throughout a person's life, but the stage from childhood to adolescence is critical because influences from peers increase while those from parents and other family members decrease. The objective of this study was to identify changes in oral health behaviours between childhood and adolescence, and investigate whether changes differed by sex. Methods: This study used data on 1860 participants from the Avon Longitudinal Study of Parents and Children (ALSPAC) who completed dental questionnaires at ages 7.5, 10.5 and 17.5 years. Associations between age and oral health behaviours were assessed using random effects logistic regression models. Males and females were analysed together or separately, depending on evidence for sex‐age interactions. Results: At age 7.5, 83% brushed their teeth frequently, 98% visited the dentist frequently and 90% drank fizzy drinks. The percentage who brushed their teeth at least twice a day decreased with age for males (odds ratio 0.96 [95% confidence interval 0.94, 0.99] per year of age) and increased with age for females (1.03 [1.01, 1.06]). Electric toothbrush usage decreased with age, with a slightly larger decrease in females (0.82 [0.80, 0.85]) than in males (0.87 [0.84, 0.90]). The percentage visiting the dentist at least once a year decreased with age (0.77 [0.73, 0.81]); the decrease was greatest between the older ages. Fizzy drink and juice consumption increased with age (1.38 [1.23, 1.57] and 1.33 [1.24, 1.44] respectively), whereas there was no change in water consumption (1.00 [0.91, 1.09]); these data were available only for the younger two ages. Conclusions: Unfavourable changes in oral health behaviours, some of which were sex‐specific, have been demonstrated in this cohort. Hence, childhood to adulthood may be an important intervening time to prevent early deterioration of oral health.